2016
DOI: 10.3390/buildings6040048
|View full text |Cite
|
Sign up to set email alerts
|

Review: Improving the Impact of Plant Science on Urban Planning and Design

Abstract: Urban planning is a vital process in determining the functionality of future cities. It is predicted that at least two thirds of the world's citizens will reside in towns and cities by the middle of this century, up from one third in the middle of the previous century. Not only is it essential to provide space for work and dwelling, but also for their well-being. Well-being is inextricably linked with the surrounding environment, and natural landscapes have a potent positive effect. For this reason, the inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 149 publications
0
18
0
Order By: Relevance
“…Over 400,000 vascular plant species have been identified [112], and so the number of urban green action designs based on combinations of plants, substrates and other supporting elements is enormous. Sustainable nature based urban design and retrofitting actions in, on, or around buildings are still in their infancy with significant amounts of new data needed to be collected and analysed by multi-disciplinary teams [138].…”
Section: Discussionmentioning
confidence: 99%
“…Over 400,000 vascular plant species have been identified [112], and so the number of urban green action designs based on combinations of plants, substrates and other supporting elements is enormous. Sustainable nature based urban design and retrofitting actions in, on, or around buildings are still in their infancy with significant amounts of new data needed to be collected and analysed by multi-disciplinary teams [138].…”
Section: Discussionmentioning
confidence: 99%
“…This has increased the interst in natural mechanisms for air filtration and the increased plantation of trees and the concept of an urban green infrastructure 57 . In extension to the contribution of parks and tree lined alleys, there is an increasing relevance of designing and implementing items of urban greenery to green roofs and facades 62 . However, as urban trees grow significantly faster than their rural conspecifics, they manifest a more rapid ageing and thus shortened lifetime which induces the need for new concepts integrating plants into megacities to ensure their contribution to the urban One of the most well-known examples for buildings in tropical zones is the passive ventilation system at the Eastgate Building, Harare, Zimbabwe -which mimics the African termite mound ventilation system by the Architect Mick Pearce 58 .…”
Section: Biomimicry Levelsmentioning
confidence: 99%
“…It was shown that a high sowing rate or a high watering rate is required for the plants to thrive during the crucial first year of operation. A somewhat unusual review by Wootton-Beard et al [97] suggests improvement regarding the contribution of plant science to the role of green infrastructure. It is suggested that architects can look to plants for solutions for the management of light, heat, water, and CO 2 in buildings.…”
Section: Management Operations and Maintenancementioning
confidence: 99%